Aeromonas hydrophila infection in silver catfish causes hyperlocomotion related to stress. (July 2019) - Bandeira Junior, Guerino; de Freitas Souza, Carine; Descovi, Sharine Nunes; Antoniazzi, Alfredo; Cargnelutti, Juliana Felipetto; Baldisserotto, Bernardo
Abstract: Aeromonosis is a fish disease that leads to haemorrhagic septicaemia and high mortality. The detection of early behavioural changes associated to this disease could be helpful in anticipating the initiation of treatment, increasing the probability of success. The influence of this disease on the hypothalamic-pituitary-interrenal (HPI) axis and on the brain expression of heat shock proteins (HSP) is little known. Therefore, the aim of this study was to evaluate the effect of Aeromonas hydrophila infection on individual behaviour and brain expression of genes related to stress ( slc6a2, hsp90, hspa12a, hsd20b, hsd11b2, crh ) in silver catfish ( Rhamdia quelen ). Thirty fish were divided into healthy and infected groups. The fish of the infected group were inoculated intramuscularly with 50 μL of bacterial suspension (6.4 × 10 8 CFU/mL), while control animals received 50 μL of saline. On day five post-infection, animals were submitted to the novel tank test, euthanized, and the brain was collected for molecular analysis. Infected fish swam more in the unknown aquarium and presented an increase in brain expression of genes related to HSP ( hspa12a ) and the route of cortisol synthesis ( crh ) when compared to uninfected fish. Therefore, this disease causes hyperlocomotion related to stress. Highlights: Aeromonas hydrophila infection in silver catfish causes increased locomotor activity. This infection also causes increased brain expression of hspa12a and crh. The disease pathophysiology involves changes in the HPI axis.